Photo Arts Concept as Alternative Photography Works - Heriwanto; Bolkiah, Muhammad Faiz; Mauludya Sudradjat, Oky (JOMANTARA, 2024)
The development of photography so far has encouraged the birth of various forms of new concepts in the field of photography. The birth of digital photography technology has provided various conveniences and encouraged photographers to develop photography more widely. Currently, the concept of photo art has been widely used by photographers or photo artists through the development of new ideas and concepts in the form of photographic works. Fine art photography can be an assessment and representation for the photographer who created the photograph. Therefore, the time has come for photographers who may or may not have unique characteristics in creating photographic works, to make photographs into works of art with a combination of new concepts in photographic work.